THE TRANSLATION OF ENGLISH DEVERBAL NOUNS IN KING JAMES BIBLE INTO MANGGARAI LANGUAGE - Fransiscus Sanur; Ketut Artawa; I Nengah Sudipa (Universitas Warmadewa, 2019)
This study aims to explain the types of shifts in the translation of English deverbal nouns (EDN) into Manggarai language especially the Central Manggarai Dialect (CMD) and to analyze how the types of EDN are translated into CMD. This study used a qualitative approach. The data were taken from the King James Bible (KJB) and Surak Nggeluk Reké Weru, English and CMD. The data were collected through observation method. This method was implemented at once with a note-taking technique. The result showed that a number of shifts and seven types of deverbal nouns found in the translation of EDN into CMD. The findings: (1) Level shifts: builders into lata pandé mbaru, (2) Structure shifts: workman into ata pala, (3) Class shifts: commandment into jera, (3) Unit shifts: healing into ina beti, and (4) Intra-system shifts: teachers into guru. In addition, the types of deverbal nouns: (1) Action deverbal noun: moving into gégon, (2) Agentive deverbal noun: beggar into ata lénggé, (3) Instrumental deverbal noun: charger into kepar, (4) Manner deverbal noun: blasphemy into rendak, (5) Locative deverbal noun: wallowing into purang, (6) Objective deverbal noun: creature into ata poli dédék, and (7) Reason deverbal noun: temperance into le kuasa weki.